أهمية الاتصال البصري في تحسين صورة المؤسسة - خلفاوي, شمس ضيات (جامعة الوادي - University of Eloued, 2018)
لقد حاولنا في دراستنا الكشف عن استخدام الاتصال البصري ومختلف دعائمه داخل المؤسسة الجزائرية، وبالخصوص تلك التي يكون منتوجها خدمة أي نيصبح عملها مرتكزا على تقديم أحسن بهدف تدعيم صورتها لدى المتعاملين معها. وكانت دراستنا بمؤسسة الخطوط الجوية الجزائرية كونها المؤسسة البارزة في السوق الوطني في قطاع السفر إضافة إلى أنها تستخدم لوغو يتواجد في كل مواقعها ومنتجاتها، وبما أنه أول مؤسس للاتصال البصري فقد قمنا بالتركيز على اللوغو و كل جوانبه إضافة إلى دعائم أخرى كالألوان لأنها تلعب دورا بارزا في نظام التعريف البصري. Summary: In our study, we tried to explore the use of visual communication and its support in the Algerian institution and especially when its product becomes a job. Thus, the latter will be based on giving the best in order to support its image to keep its customs. The study was conducted at “Algerian Airways” since it is the famous national institution in the domain of travelling, in addition it uses a Logo in all its sites and products, and since it is the first founder of visual communication .We concentrated on the Logo because it plays a major role in the system of visual definition.
مقال
Keywords: الاتصال البصري، صورة المؤسسة، اللوغوتيب، الاتصال